Gendering Labour Law in the Platform Economy: Supporting Women Crowdworkers through Motherhood - Al James (Labour & Law Issues)
This article challenges the stubborn analytical invisibility of women within platform labour studies and platform labour law, by making visible the gendered reproductive dynamics of paid and unpaid labour on digital labour platforms. The analysis is built from 5 years of research with women crowdworkers in the UK. First, the article reviews recent debates in platform labour law concerned to extend employee welfare protections to ‘independent’ platform workers, including nascent feminist interventions that seek to bring women and gender relations to the centre of those debates. So motivated, the second part of the article makes visible women’s shifting experiences of crowdworking as ‘independent’ self-employed freelancers with young children at different moments of the lifecourse, and the origins and outcomes of these women’s exclusion from labour law designed to protect women employees. Third, the analysis identifies a series of ‘digital agency practices’ and ‘tactical workarounds’ through which women crowdworkers are able to improve their everyday conditions of work and self-employment during pregnancy, maternity and beyond, in the absence of legal protection. The article also sets out women’s suggestions for concrete changes that would improve their everyday work-lives, including the need to expand the scope of platform labour law to include provision for pregnancy, maternity, and post-maternity return – or else remain ineffective and marginal to the needs of millions of women crowdworkers worldwide.